EFFECTIVENESS CONSTRUCTIVIST LEARNING TO IMPROVE RESULTS SUBJECT AUTOMOTIVE ELECTRICAL MAINTENANCE AND REPAIR CLASS XI AUTOMOTIVE ENGINEERING DEPARTMENT IN SMK MUHAMMADIYAH 1 IMOGIRI ACADEMIC YEAR 2013/2014 - Komal Hadi; Subagyo Subagyo (Universitas Sarjanawiyata Tamansiswa, 2013)
This study aims to determine student learning outcomes in subjects automotive electrical repair and maintenance before and after the application of constructivist learning and to determine the improvement of student learning outcomes in subjects automotive electrical maintenance and repair in SMK Muhammadiyah 1 Imogiri, after the application of constructivist learning. Hypothesis of this research is the application of constructivist learning can improve learning outcomes of students of class XI Automotive Engineering Department at SMK Muhammadiyah 1 Imogiri. This type of research is quasi experimental. The sample used in this research are all students of class XI TKR 1, amounting to 35 people as the experimental group, all students of class XI TKR 2, amounting to 36 people as a group kontrol. Teknik data capture using objective tests. The validity of the research instruments performed by analysis of grain which is calculated by the formula product moment correlation. Reliability of the instrument is calculated using the formula KR-20. Data analysis techniques are used to test hypotheses independent sample t-test or Mann Whitney. The results showed that there was no difference in student learning outcomes in subjects automotive electrical maintenance and repair in SMK Muhammadiyah 1 Imogiri, prior to the constructivist learning control class is 50.43 and 50.00 for the experimental class ( p > 0.05 ). There is a difference in student learning outcomes in subjects automotive electrical maintenance and repair in SMK Muhammadiyah 1 Imogiri, constructivist learning in the classroom after the control was 63.29 and 76.53 for the experimental class ( p < 0.05 ). There is an increase in student learning outcomes in subjects automotive electrical maintenance and repair in SMK Muhammadiyah 1 Imogiri, after the application of constructivist learning. Improved student learning outcomes in the classroom lecture method was 12.86 ( 25.50 % ) and the class that uses the constructivist method was 26.53 ( 53.06 % ).